Birth of first foals through embryo transfer after artificial insemination using frozen semen in Japan - HANNAN, M A (J Reprod Dev, 2020)
Until now, there have been no reports of foals born through embryo transfer after artificial insemination using frozen semen in Japan. The aims of this study were to develop a riding crossbred horse and evaluate the prospects of embryo transfer technology in multiplying horse population. In both donor and recipient mares, luteolysis was induced by the administration of 0.1 mg Cloprostenol to synchronize the onset of estrus, and ovulation was induced by administering 2000 IU human chorionic gonadotropin (hCG) or 0.75 mg Deslorelin. Frozen semen from an Irish Connemara pony stallion was used to breed a Hokkaido native pony mare by deep-horn artificial insemination (dose, 400 × 10(6) sperm). A non-surgical technique was used to collect embryos from the donor mare at day 7 post-ovulation and transfer them transcervically into the uterus of recipient mares (n = 4) immediately after collection. Weekly blood samples were collected from the recipients throughout pregnancy. A total of four embryos were recovered from seven collection attempts (57% recovery) from a donor mare in a single breeding season. Three of the four transferred embryos maintained successful pregnancy and delivered a healthy live foal (75% birth). A normal progesterone profile was observed throughout gestation in recipient mares. In conclusion, for the first time, to the best of our knowledge, this study describes the birth of foals through non-surgical transcervical embryo transfer in Japan after artificial insemination using frozen semen. We expect that this new crossbreed (Connemara pony × Hokkaido native pony) will be a good riding breed.